Internet of Things (IoT), Sejarah, Teknologi, dan Penerapannya - Ayu Syahfitri (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The Internet of Things (IoT) is a cutting-edge technology that refers to various devices and systems around the world that are interconnected via the internet to share data. This technology involves the use of sensors and communication software to control, connect, and transfer data between devices by utilizing internet networks, enabling performance without direct supervision. In machine-to-machine (M2M) terms, (1) IoT can be defined as a technology that integrates various devices to improve efficiency and convenience; (2) its working method involves automatic connection and communication between devices; and (3) the research objectives are exploratory to understand its benefits. Some of the benefits of IoT include its ability to support people's daily lives through automation and efficiency. (4) Examples of its application can be found in various aspects of life, such as smart homes, healthcare, and transportation. (5) Based on the development history and previous research summarized in this journal, IoT is an advanced technology designed to simplify their daily activities.